2011
DOI: 10.1093/cvr/cvr010
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of p27kip1 contributes to Nrf2-mediated protection against angiotensin II-induced cardiac hypertrophy

Abstract: The Nrf2-p27(kip1) pathway serves as a novel negative feedback mechanism in Ang II-induced pathogenesis of cardiac hypertrophy, independent of changes in blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 38 publications
5
58
0
Order By: Relevance
“…(53,54). Consistent with previous observations that Nrf2 deficiency leads to an earlier onset of cardiac pathological remodeling and the subsequent development of heart failure in response to hemodynamic overload or pharmacologically induced cardiac stress (55,56), Wang et al found that the cardiomyocyte-specific overexpression of Nrf2 suppressed myocardial oxidative stress as well as cardiac apoptosis, fibrosis, hypertrophy, and dysfunction in a setting of sustained pressure overload produced by transverse aortic constriction (53). Interestingly, the constitutive activation of Nrf2 increased the steady level of autophagosomes while decreasing ubiquitinated protein levels and ubiquitin-positive protein aggregates in the pressure overloaded heart.…”
Section: Nrf2 In Autophagysupporting
confidence: 89%
“…(53,54). Consistent with previous observations that Nrf2 deficiency leads to an earlier onset of cardiac pathological remodeling and the subsequent development of heart failure in response to hemodynamic overload or pharmacologically induced cardiac stress (55,56), Wang et al found that the cardiomyocyte-specific overexpression of Nrf2 suppressed myocardial oxidative stress as well as cardiac apoptosis, fibrosis, hypertrophy, and dysfunction in a setting of sustained pressure overload produced by transverse aortic constriction (53). Interestingly, the constitutive activation of Nrf2 increased the steady level of autophagosomes while decreasing ubiquitinated protein levels and ubiquitin-positive protein aggregates in the pressure overloaded heart.…”
Section: Nrf2 In Autophagysupporting
confidence: 89%
“…Further investigation indicated that miR-221-induced cardiac remodeling is associated with the downregulation of p27, activation of the mTOR pathway, and the subsequent inhibition of autophagy in cardiomyocytes [3]. The p27 gene is robustly expressed in adult cardiomyocytes, and it plays an anti-hypertrophic role in response to adverse stimulations [4][5][6]. Furthermore, p27 was also found to protect cardiomyocytes from apoptosis by inducing autophagy during metabolic stress [7].…”
Section: Cardiac-specific Overexpression Of Mir-222 Induces Heart Faimentioning
confidence: 99%
“…Similarly, angiotensin II (Ang II)-induced cardiac hypertrophy (77), and cell death caused by I/R injury (136) were both exacerbated in Nrf2-null mice. In the case of Ang II-induced hypertrophy, a functional interaction between Nrf2 and the cell cycle regulator, p27, in the inhibition of hypertrophy was demonstrated (77).…”
Section: Oxido-reductive Pathways In Heartmentioning
confidence: 99%
“…Similarly, angiotensin II (Ang II)-induced cardiac hypertrophy (77), and cell death caused by I/R injury (136) were both exacerbated in Nrf2-null mice. In the case of Ang II-induced hypertrophy, a functional interaction between Nrf2 and the cell cycle regulator, p27, in the inhibition of hypertrophy was demonstrated (77). In general, the deleterious effects of Nrf2 ablation upon cardiac function have been ascribed to decreased levels of antioxidant and detoxifying enzymes resulting in excess oxidant-mediated damage after ROS-induced cardiac stress.…”
Section: Oxido-reductive Pathways In Heartmentioning
confidence: 99%